2000
DOI: 10.1093/jac/46.2.283
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Helicobacter pylori to mupirocin, oxazolidinones, quinupristin/dalfopristin and new quinolones

Abstract: The in vitro activities of mupirocin, quinupristin/dalfopristin, linezolid, eperezolid, sitafloxacin, clinafloxacin, moxifloxacin, amoxycillin, metronidazole and clarithromycin were tested at pH 7.4 against 57 strains of Helicobacter pylori. The most active agents (mupirocin, sitafloxacin and clinafloxacin) were also tested for activity at pH 5.4 against the same strains. Mupirocin was very active at pH 7.4 and 5.4 (MIC90 0.25 and 0.12 mg/L, respectively). Quinupristin/dalfopristin, linezolid and eperezolid ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 9 publications
3
51
0
1
Order By: Relevance
“…Fluoroquinolones have in vitro activity against Hp (24). A recent in vitro study also showed a synergistic effect of quinolone antimicrobial agents and PPIs on strains of Hp (25).…”
Section: Discussionmentioning
confidence: 97%
“…Fluoroquinolones have in vitro activity against Hp (24). A recent in vitro study also showed a synergistic effect of quinolone antimicrobial agents and PPIs on strains of Hp (25).…”
Section: Discussionmentioning
confidence: 97%
“…Furazolidone has also been proposed but it is associated with important adverse events too. 23 Fluoroquinolones have been shown in vitro to be actives drugs against H. pylori, 24 and different studies confirmed the efficacy of regimens containing levofloxacin as first-line treatment. 25,26 A recent in vitro study also showed a synergistic effect of quinolone antimicrobial agents and PPIs on 17 strains of H. pylori.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, some studies have evaluated the efficacy of new fluoroquinolones, such as levofloxacin, that could prove to be a valid alternative to standard antibiotics, not only as first-line therapies, but more interestingly, as second-line regimens [21,[88][89][90] . In this respect, levofloxacin-based second-line therapies represent an encouraging strategy for eradication failures, as some studies have demonstrated that levofloxacin has, in vitro, remarkable activity against H pylori [91] , and that primary resistances to such an antibiotic are (still) relatively infrequent (when compared with metronidazole or clarithromycin) [92][93][94][95][96] . A recent in vitro study also showed a synergistic effect of quinolone antimicrobial agents and PPIs on strains of H pylori [97] .…”
Section: Rbc Tetracycline and Metronidazolementioning
confidence: 99%